Tribo‐corrosion mechanisms and electromechanical behaviours for metal implants materials of CoCrMo, Ti6Al4V and Ti15Mo alloys. Issue 1 (26th January 2022) - Wang, Hongxiang; Zheng, Jingjing; Sun, Xiaolei; Luo, Yong
Abstract: Corrosion and wear play significant roles in the aseptic loosening of artificial hip joints for the long‐term service. In this present study, tribo‐corrosion tests were carried out through a reciprocating ball‐on‐plate system to evaluate the corrosion and wear properties of CoCrMo, Ti6Al4V and Ti15Mo alloys in a simulated body fluid (SBF) solution. It was found that the tribo‐corrosion behaviours of CoCrMo/Al2 O3 and Ti15Mo/Al2 O3 systems had significant wear‐corrosion synergistic interaction, and wear‐induced corrosion was dominant. For Ti6Al4V/Al2 O3 systems, their wear mechanism under SBF lubrication was a combination of abrasive, adhesive and fatigue wear. While the wear mechanism of the Ti15Mo/Al2 O3 system under synergistic interaction was a combination of abrasive and adhesive wear. Finally, it was suggested that the Ti15Mo alloy would be the better alternative for metal implant applications compared with the CoCrMo alloy for the consideration of both wear and potential poisonous ions such as Co(III) and Cr(VI).